Since 1948 : Israeli literature in the making - Berg, Nancy E.; Sokoloff, Naomi B. (SUNY Press, State University of New York, 2020)
"Argues for stretching the boundaries of Israeli literature linguistically, geographically, and generically"-- Provided by publisher.
Keywords: Israeli literature -- History and criticism.; Littérature israélienne -- Histoire et critique.; Middle Eastern.; Jewish.; LITERARY CRITICISM.; Jewish Studies.; SOCIAL SCIENCE.; Israeli literature; Electronic books.; Criticism, interpretation, etc.